PENGARUH TINGKAT PEMBATASAN PEMBERIAN PAKAN (Restricted Feeding) TERHADAP PERFORMAN AYAM BROILER JANTAN - Hatifah Aprilia Kusuma; Ashry Mukhtar; Ratih Dewanti (Universitas Sebelas Maret (UNS), 2016)
This study aims to determine the effect of restricted feeding rate on the broiler chickens performance. The research was carried out in Tompe, Jirapan Village, Masaran Sub District, Sragen Distric for six weeks beginning from September 14th until October 26th, 2011. This study used 100 male broiler chickens New Lohmann strain. The research design used Completely Randomized Design (CRD) one way trafic with four treatments. The fourth treatments are: P0 (full feeding without fasting), P1 (6 days full feeding and 1 day fasting), P2 (5 days full feeding and 1 day fasting) and P3 (4 days full feeding and 1 day fasting). Each treatment consisted of five replicates. Feed consisted of BR1 and BR2. The Parameters observedare Body Weights Gain, Feed Consumption, Feed Conversion,and Income Over Feed Cost. The results showed that the average of four treatment are P0, P1, P2 and P3 respectively for body weight gain are 81.37; 74.47; 72.65, and 72.50 grams / head / day, feed intake are 137.94; 126.46; 124.06; and 119.11 g / head / day, feed conversion are 1.70; 1.70; 1.71, and 1.64, feed efficiency are 0.59; 0, 59; 0.59, and 0,61. The average of Income Over Feed Cost are Rp. 8.757,26; Rp. 8.014,98;Rp. 7.818,14; and Rp. 7.808,57. The analysis of variance results for body weight gain and whole consumption has significant effect (P<0.01), conversionwas not affected. From these results it can be concluded that the rate of feeding restricteds is significantly affect on body weight gain and feed consumption of Broiler Males.